A geo-linguistic approach to a historical analysis of the economic trade-partners of the residents in the Zamboanga del Norte and Misamis Occidental strip - Campiseño, Evelyn R. (The Threshold: the Official Research Journal of Jose Rizal Memorial State University, Zamboanga del Norte, 2012)
This study investigated the economic partnerships among the traders in Zamboanga del Norte and Misamis Occidental strip through a geo-linguistic approach. Descriptive-survey method of research was employed. The oldest traders from each locality were interviewed and the data gathered were presented using the percentage, frequency distribution and attribution analysis. It revealed that majority of the traders having business tie-ups were coming from Ozamis City and Dipolog City despite the geographical distance between the two cities; office and school supplies ranked first among the commodities being bartered; Cebuano and Mandarin were the languages commonly spoken by the abovementioned traders. This result is accounted to the language spoken with 38.7 percent of attribution; 35 percent for the population size and 26.3 percent for the number of schools existing in the localities. It implies that the commonality of language between traders is a topmost consideration in forging business partnership by common understanding as well as the number of people and institutions in the locality that would directly be responsible for the bulk of demand and consumption of the goods being traded.